Economic Contribution of the Department of Agriculture 4K Program of Local Government Unit in Southern Philippines: Basis for Program Enhancement - Bandahan Mary Rose P.; Dumaog Czharralhyn Davone L.; Carlos Angelene C.; Lubos Lalevie C. (SHS Web of Conferences)
This study determines the economic contribution of the Department of Agriculture’s 4K (Kabuhayan at Kaunlaran ng Kababayang Katutubo) program to beneficiaries of Local government unit in Southern Philippines, an Indigenous community. It also assesses the program’s impact on beneficiaries’ economic conditions before and after participation, including satisfaction of basic needs, support for education, access to credit, acquisition of assets and properties, rest and recreation, healthcare, life insurance, savings, and investments. The study employed quantitative research methods and utilized a survey questionnaire to evaluate beneficiaries’ economic conditions before and after participating in the 4K program through simple random sampling. The findings reveal significant improvements in beneficiaries’ economic conditions after participating in the Department of Agriculture’s 4K program. Before participation, beneficiaries exhibited limited economic capacity, whereas post-program results indicate enhanced capacity to satisfy basic needs and support education. The study underscores the substantial contribution of the Department of Agriculture’s 4K program to the economic well-being of beneficiaries. It recommends continuous support from the Department to identify areas for program enhancement, to provide communities with the tools they need to choose and create livelihood initiatives that fit their resources, abilities, and cultural values.